Factors Analysis of Exclusive Breastfeeding Through Breastfeeding Self-Efficacy in Pemalang - Fitriana, Nana; Raharjo, Bambang Budi; Wijayanti, Yuni (Public Health Perspective Journal, 2021)
Exclusive breastfeeding is giving only breast milk without giving other food and drinks to babies from birth to 6 months of age and can be given until the age of 2 years. Breastfeeding coverage in Central Java tends to be low, namely in 2018 (45.21%). Dai Pemalang in 2015 (56.68%), 2016 (31.42%), 2017 (37.61%), 2018 (23.32%), 2019 (31.6%). The research objective was to analyze the factors that influence exclusive breastfeeding in Pemalang. This study used a cross-sectional design. The research sample of 110 respondents was obtained by using the cluster random sampling technique. Data collection techniques are interviews, observation, questionnaires. Data analysis in the study used the Chi-Square test and multivariate analysis. The results showed that the experience of breastfeeding and verbal persuasion had a direct or indirect effect on exclusive breastfeeding. The factor of observation of other people and verbal persuasion does not affect exclusive breastfeeding. Breastfeeding self-efficacy has a direct effect on exclusive breastfeeding with values (b = 3.82; 95% CI = 1.56 to 6.07; p = 0.001). The public health center in Pemalang needs to improve education for mothers and the community, including giving to husbands of breastfeeding mothers and the community.